A independência e a autonomia dos bancos centrais - Aragão, Francisco Paulo Brandão (2007)
The objective of this dissertation aims the independence and autonomy of the central banks. Distributed into three chapters, the first one is dedicated to the classic functions of the central banks; the second, to the appearing of the Central Bank of Brazil, referring to the performance of Banco do Brasil as such, the Bretton Woods Conference and the Superintendência da Moeda e do Crédito (SUMOC). And to the Bretton Woods system of fixed parities and its decay; and the third to the independence of the central banks and correlate criticism, as well as to their autonomy, and discoursing about them in the Comparative Law. For that we looked for help into the Brazilian and foreign doctrine on Banking Law and the severalworks about Money and Banks, including specialized articles. After examining the two main central bank models defended presently – autonomous and independent -, we came to the conclusion that the model to be implemented is the autonomous, endowed of independence of instruments but not of goals.This choice avoids the formation os a fourth power practically apart from the system of bridles and counterweights and to the social reality, once money is not neutral.